ChemInform Abstract: A Method for the Synthesis of Pyridines from Aldehydes, Alkynes and NH4OAc Involving Rh‐Catalyzed Hydroacylation and N‐Annulation. Issue 14 (20th March 2013) - Sim, Yong‐Kyun; Lee, Hyejeong; Park, Jung‐Woo; Kim, Dong‐Su; Jun, Chul‐Ho
Abstract The route to the pyridine derivatives includes the hydroacylation reaction of aldehydes with internal or terminal alkynes followed by the annulation with the symmetrical internal alkyne and a nitrogen source.